Penggunaan Metode Techique for Order Preference by Similarity to Ideal Solution (TOPSIS) untuk Evaluasi Kinerja Dosen oleh Mahasiswa (Studi Kasus: STMIK Lombok) - Fadli, Sofiansyah; Zaen, Mohammad Taufan Asri (JISA(Jurnal Informatika dan Sains), 2018)
In general the lecturers performance evaluation is a routinity of a College institute for improving internal quality on an ongoing basis as well as the improvement of the status of accreditation. Performance evaluation activities specifically lecturer at STMIK Lombok funded on each period, that is the end of each semester, the lecturers assessment process performed by the students. The results of this performance assessment will be use to improve the performance of evaluation material and any lecturer who was elected as a lecturer with the best performance will be given the award. To assist in the assessment process, a system that capable to support the decision of the performance assessment of lecturers needed. The purpose of this research is to evaluate the performance of Lecturers by students at STMIK Lombok. The decision-making process aided by a computerized decision support system in expectation that subjectivity in decision-making can be minimised. Decision support systems can be used as a tool for evaluating the performance of the lecturers, so hopefully it can help the policy makers in decision-making, to get objective information about the performance of lecturers based on specified criteria.